Effectiveness of the Independent Learning Curriculum On Students' Creative Thinking Skills - Syofiyanti, Dessy; Helina Apriyani; Dewi; Indra Syahputri; Refa Lestari; Tri Revita Sari; Umi Halimatun Sa’diyah (Global Action and Education for Society, 2026)
The main problem in education today lies in the low level of students' creative thinking skills, as demonstrated by various national and international assessment results. This indicates a gap between curriculum objectives and expected learning outcomes. The Independent Learning Curriculum (Merdeka Belajar) is presented as a solution to create flexible, innovative, and student-centered learning, but its implementation in the field still faces various obstacles such as a lack of teacher understanding, inadequate learning facilities, and less than optimal student engagement. Based on these conditions, this study aims to analyze the effectiveness of the Independent Learning Curriculum implementation in improving students' creative thinking skills at SMP Negeri 3 Rengat. This study aims to analyze the effectiveness of the Independent Learning Curriculum implementation in improving students' creative thinking skills at SMP Negeri 3 Rengat. This study uses a qualitative approach with descriptive methods, involving teachers and students as informants through interviews and observations. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that teachers have implemented the Merdeka Belajar Curriculum steps by preparing lesson plans, teaching modules, learning methods, and assessment systems. Furthermore, students demonstrated creative thinking skills by presenting novel ideas, viewing problems from multiple perspectives, and actively engaging in learning projects. The study concluded that the Independent Learning Curriculum has proven effective in improving students' creative thinking skills, although improved facilities, teacher training, and more comprehensive learning strategies are still needed for optimal implementation.